A new fear in wine: Isolation of Staphylococcus epidermidis histamine producer. (April 2016) - Benavent-Gil, Yaiza; Berbegal, Carmen; Lucio, Olga; Pardo, Isabel; Ferrer, Sergi
Abstract: Biogenic amines (BAs) are undesirable compounds in all foods and beverages because they may induce food-borne intoxications when consumed at high concentrations. The aim of this study was to identify the organism responsible for the synthesis of histamine in a Tempranillo red wine from Ribera de Duero D.O. (Denomination of origin), Spain. Bacteria present in wines after malolactic fermentation were isolated, identified and typed. Four strains of the species Oenococcus oeni and two strains of Staphylococcus epidermidis were found. None of the O. oeni strains produced histamine, cadaverine or putrescine, but one of the S. epidermidis strains (Pa) was able to produce all three in synthetic medium and grape must, although not in wine. From the data obtained in this work, histamine present in Tempranillo wine B was produced by the S. epidermidis strain Pa. This is the first report in which the presence of S. epidermidis has been reported in wine and whose ability to produce histamine, putrescine and cadaverine has been demonstrated in grape must. Highlights: Two strains of Staphylococcus epidermidis, Pa and Pb, have been isolated from a Tempranillo wine. Wine containing S. epidermidis had higher histamine quantity than the other wine. S. epidermidis Pa was able to produce histamine in H-MDB mod medium and grape must.